The Effect of Emotional Intelligence, Self-Efficacy, Subjective Well-Being and Resilience on Student Teachers’ Perceived Practicum Stress: A Malaysian Case Study - Geok, Kim Ngui; Lay, Yoon Fah (2020)
Stress is inevitable in the world of teaching and practicum training and therefore, student teachers naturally incur a certain level of stress due to the demands for them to use various knowledge and skills in real school and classroom environment. Hence, practicum stress needs to be addressed accordingly. The central focus of this study is using a partial least square-structural equation modeling to explore the inter-relationships among the student teachers’ personal resources to mitigate practicum stress. A sample of 200 student teachers selected by purposive sampling from teacher education institutions in Sabah, Malaysia was used in this study. This study collected data via survey methods using a questionnaire developed from several existing scales. Findings showed that emotional intelligence, self-efficacy, and subjective well-being were able to explain resilience with good predictive accuracy and relevance but poorly for practicum stress. These findings were suggestive of the need to include additional constructs to explain perceived practicum stress better in future exploratory research.